2018
DOI: 10.4000/cea.3015
|View full text |Cite
|
Sign up to set email alerts
|

Varying Presence, Diverging Approaches: The influence of the emerging powers on health cooperation in Mozambique

Abstract: O trabalho Cadernos de Estudos Africanos está licenciado com uma Licença Creative Commons-Atribuição-NãoComercial-CompartilhaIgual 4.0 Internacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The methodology included a broad review of the available academic and policy literature on the PAEN, as well as data collection and analysis in one specific country, Mozambique. Preliminary studies into the Indian development co-operation in health and in Southern Africa indicated that Mozambique was an interesting and likely case study (see De Bruyn 2013a, 2013b, 2014, 2016a, 2016b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology included a broad review of the available academic and policy literature on the PAEN, as well as data collection and analysis in one specific country, Mozambique. Preliminary studies into the Indian development co-operation in health and in Southern Africa indicated that Mozambique was an interesting and likely case study (see De Bruyn 2013a, 2013b, 2014, 2016a, 2016b).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the Indian pharmaceutical companies exporting generic medicines to Mozambique, there are a few private Indian hospitals, or hospitals employing India practitioners in Maputo, providing mainly tertiary health services. One of the new entrees is the Dr Agarwal eye hospital (De Bruyn 2016b). This is one of the main chains of eye care centres and hospitals in India.…”
Section: Underlying Rationale For Co-operationmentioning
confidence: 99%